Histoculture drug response assay predicts chemotherapy efficacy and improves survival in gastrointestinal cancers - Wang, Shuang; Fan, Na; Li, Han; Li, Yang; Hu, Ping; Chen, Dongliang; Jiang, Xiaohong; Gao, Lei; Yang, Chenggang; Yang, Dawei (Frontiers in Oncology, 2025)
BackgroundThe high incidence, substantial mortality, and marked heterogeneity in chemotherapy responses among gastrointestinal tumors accentuate the imperative for individualized treatment strategies. This study aims to evaluate the reliability and clinical significance of the histoculture drug response assay (HDRA) in predicting chemotherapy sensitivity and prognosis. Specifically, it focuses on Chinese patients diagnosed with gastrointestinal cancers.MethodsThis study enrolled 283 patients with gastrointestinal tumors, comprising 124 esophageal cancer cases, 92 gastric/cardia cancer cases, and 67 colorectal cancer cases. Immunohistochemistry was conducted to assess tumor structure integrity and the expression of Ki - 67, CD31, and E - cadherin before and after the HDRA assay. HDRA evaluated the efficacy and inhibition rates of single and combination chemotherapy regimens. Moreover, the effect of HDRA - guided treatment on patient survival was analyzed.ResultsThe results indicated that HDRA effectively preserved the three-dimensional structure and microenvironment of gastrointestinal tumors, as no significant changes were observed in the expression of Ki-67, CD31, or E-cadherin. Furthermore, combination regimens showed significantly higher efficacy and inhibition rates than single - agent therapies. Notably, platinum-based combination therapy was most effective in esophageal cancer. Survival analysis revealed that esophageal and gastric cancer patients receiving HDRA - sensitive regimens (HDRA group) had significantly longer disease - free survival (DFS) compared to those on non - sensitive regimens (N - HDRA group) and untreated patients. Cox regression analysis indicated that HDRA-guided treatment serves as a protective factor for DFS (hazard ratio, HR<1).ConclusionIn summary, the HDRA assay represents a reliable assay for accurately evaluating chemotherapy regimens, thereby furnishing guidance for individualized treatment in gastrointestinal cancer patients.